Education Support Program (ESP): forming partnership for education, Sept. 1, 1991 to April 31, 1999 - BRAC (© BRAC, 2016)
1. Introduction 2. Rationale for undertaking ESP 3. Goal of ESP 4. Objectives of ESP 5. The ESP partners 6. Criteria for selecting partner NGOs 7. The ESP funded schools 8. Management of ESP 9. Cost of ESP NFPE 10. Concluding remarks.